Metoda kształtowania ustrojów cięgnowych osiowo-symetrycznych - Jendo, S. (Engineering Transactions, 1969)
The subject of the present work is the determination of the shape of axially-symmetrical surface suspended structures and its optimization according to the criterion of minimum weight. Due to the axial symmetry of the structure and load, determination of the shape of the surface can be reduced to the determination of the shape of carrying cables with orientation south. The shape of carrying ties has been expressed in closed form by known special functions (errorfunctions).Furthermore, the solution of the problem has been programmed for the GIER computer usingthe ALGOL code. Numerical solutions have been obtained for geometrical parameters frequently found in practice. The results are presented in tables and graphs.